The winding road of social entrepreneurship definitions: a systematic literature review. Issue 2 (1st August 2016) - CONWAY DATO-ON, MARY; Kalakay, Jerrid
Abstract : Purpose: The study contributes to understanding social entrepreneurship via a systematic literature review (SLR) of the construct's varied definitions to assess the means by and the context in which the phenomenon is studied. Design/methodology/approach: The systematic literature review (SLR) follows a deliberative, replicable, methodical, and transparent process, including a quality assessment tool or definitional sources. SLR results are organized around Gartner's (1985) framework of new value creation, thus additionally analysing the dimensionality with which social entrepreneurship has been studied. Finally, a qualitative analysis of the definitions reviews commonalities of themes within definitions to assess trends. Findings: Significant research has been dedicated to defining social entrepreneurship. However, many efforts do not explore the full dimensionality of the concept, as findings reveal that no definition explored the four dimensions of entrepreneurship posited by Gartner (1985). Further, time-series review of definitions demonstrates limited advancement in definitional development. Geographic location of definition authors and key word analysis challenge previous research on the activation of social entrepreneurship in literature. Research limitations/implications: Although the SLR was conducted in a controlled manner, this study is time bound and only reviews English-language publications. While results are analysed using a recognized framework (i.e., Gartner 1985), other conceptual models are available. Although two researchers independently categorized and analyzed definitions, assessment of quality was limited. Results offer insight into how the conceptualization of social entrepreneurship may be advanced as well as the important role of practitioners in development of the construct's theory and practice. Practical implications: The detailed appraisal of definitions may guide practitioners as they strive to define their own organizational efforts. The multi-dimensional conversation of social entrepreneurship in this study enables leaders of different organizational types to ensure their social entrepreneurship activities consider all dimensions (i.e., environment, individual, organization, and process). The SLR allows the practitioner to further engage in deep discussion on the future of the field by cataloguing their influence on the multi-dimensionality of the social entrepreneurship construct. Organizational leaders may also use the findings to generate more discussion around what is missing from the definitions (i.e., empathy, responsibility, resourcefulness, transparency). Originality/value: Findings synthesize social entrepreneurship definitions across multi-disciplinary fields, contexts, and within a multi-dimensional framework utilizing an infrequently employed literature review method within social sciences.